The Erosion of Customary Authority and The Riset of Local Ulama In The Normalization of Unregistered Marriages In Indonesian Muslim Communities - Safrin Salam; Nurul Miqat; Risma Yulestari; Ibrahim Kayode Muhammed; Callistus Odeh (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
This study examines the erosion of customary authority and the repositioning of local clerics in legitimizing unrecorded marriage in the Indonesian Muslim community in the context of legal pluralism and modernization. The research is directed to understand how the relationship between customary institutions, religious authorities, and state law reshapes the legitimacy of marriage and legal awareness in contemporary Islamic family law. This study uses a qualitative socio-legal approach based on legal anthropology and sociology of religion, with a comparative case study design on several Muslim communities in Indonesia where the practice of marriage is not recorded as still persisting. Data were collected through in-depth interviews, document analysis, and limited participatory observation. The results show that customary authorities are weakened due to modernization, bureaucratization of marriage administration, migration, generational change, and declining effectiveness of collective sanctions. In this situation, local clerics increasingly occupy a central position as determinants of the legitimacy of marriage through mosque-based authority, religious education networks, and moral leadership. This configuration gives birth to a layered legal landscape, where state law, customary practices, and religious norms coexist unequally, so that social legitimacy by scholars can outweigh weakened customary sanctions and uneven enforcement of state law. This study concludes that the normalization of marriage is not just an administrative failure, but a manifestation of a shift in normative authority in Indonesia's plural legal order. In practice, the study recommends strengthening cooperation between state institutions, indigenous actors, and scholars to improve marriage registration, strengthen legal awareness, and protect the rights of women, children, and families.